In Salmonella enterica, OatA (Formerly YjgM) Uses O-Acetyl-Serine and Acetyl-CoA to Synthesize N,O-Diacetylserine, Which Upregulates Cysteine Biosynthesis - VanDrisse, Chelsey M.; Escalante-Semerena, Jorge C. (Frontiers in Microbiology, 2018)
L-cysteine biosynthesis has been extensively analyzed in Salmonella enterica. The cysteine regulon contains the genes whose protein products are necessary to convert sulfate to sulfide, which is eventually reacted with O-acetyl-serine (OAS) to generate cysteine. The LysR type regulator, CysB, is required for activation of the cysteine regulon, and its interaction with various cys genes has been thoroughly characterized. Results from previous studies by others, suggested that OAS undergoes a spontaneous O- to N- migration to produce N-acetyl-serine (NAS), and that NAS is the true signal sensed by CysB. It was unclear, however, whether such migration occurred spontaneously in vivo or if NAS was generated enzymatically. Work reported herein characterizes a S. enterica N-acetyltransferase, OatA (formerly YjgM), which acetylates the Nalpha-amino group of OAS, producing N,O-diacetyl-serine (DAS) at the expense of acetyl-CoA. We isolated OatA to homogeneity and performed its initial biochemical characterization. The product of the OatA reaction was isolated by HPLC and confirmed by mass spectrometry to be DAS; OatA did not acetylate NAS, consistent with the conclusion that OatA is an N-acetyltransferase, not an O-acetyltransferase. Binding of OAS to OatA appears to be positively cooperative with the apparent K0.5 for OAS determined to be 0.74 mM, the kcat was 1.05 s-1, and the catalytic efficiency of the enzyme (kcat/K0.5) was 1.4 x 103 M-1 s-1. Size exclusion chromatography indicated that OatA was a monomer in solution. In S. enterica, overexpression of oatA led to shorter lag times on sulfate-limiting medium and that these delayed lag times were due to increased expression of the cysteine regulon, as indicated by RT-qPCR results. OatA is the first Gcn5-related N-¬acetyltransferase (aka GNAT) involved in the regulation of amino acid biosynthetic genes in Salmonella. On the basis of results of transcriptomics studies performed by other investigators, we hypothesize that DAS may play a role in biofilm formation in S. enterica and other bacteria.